Wound healing of the laterally positioned flap: A histomorphometric assessment (2015)
he aim of this study was to histomorphometrically assess the soft tissue anatomy in single gingival recessions (GR) treated with a laterally positioned flap (LPF). Five patients presenting maxillary first molars with GR to the apex of the buccal surface of the mesial-buccal root were invited to take part. The LPF-treated roots were removed en bloc (the root and the soft tissue covering the treated GR) 3 to 4 months postoperatively. Photomicrographs of Mallory trichrome stain sections were taken to allow reassessment of the specimens regarding the longitudinal dimensions of the crevicular/sulcular and junctional epithelia. The use of LPF resulted in new attachment with formation of crevicular epithelium, long junctional epithelium, and some connective tissue, re-establishing the normal anatomical characteristics of the soft tissues covering the previously exposed root.